Chapter Identità narrativa e memoria autobiografica: prospettive per un dialogo interdisciplinare - FEYLES, MARTINO MARIA (Moderna/Comparata, 2022)
The essay proposes a reflection on narrative and storytelling, on the idea of the subject and personal identity, based on Ricoeur's philosophy but from a broader constructivist and bio-psycho-social perspective. Narrative as the construction of meaning and the construction of coherence becomes, in this sense, a lens through which to look at the new philosophies of mind and their fruitful interaction with psychology and cognitive neuroscience.